Description of Mother's Behavior and Nutritional Status of Toddlers After the Nutrition Recovery Program in Makassar City, South Sulawesi - Ramli, Rachmat; Srifitayani, Nur Rahma; Kristina, Yunita; Reffita, Lea Ingne; Rohemah, Rohemah; Afrika, Eka; Hikmah, Mutiara (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The nutrition recovery program is one of the efforts to overcome malnutrition in children by involving mothers or families. Mothers are provided with knowledge so that they can become independent in caring for and providing additional food that has been provided or recommended by the health center. During the three months, there were still children who did not experience changes in nutritional status, namely very thin, and only a few children experienced changes in nutritional status to become thin and normal. This type of research is a survey with a cross-sectional research design and aims to determine the description of maternal behavior and the nutritional status of toddlers after the nutritional recovery program in Makassar City. The method used is descriptive analysis. Data was collected by direct interviews with mothers using questionnaires. The child's weight was measured using a step scale and the child's height using a measuring board and microtoise. Nutritional status is measured by the BB/TB indicator. The research results showed that most of the mothers' knowledge was in the sufficient category, the mothers' attitudes were in the sufficient category, and the mothers' actions were in the sufficient category. Officers are expected to further increase mothers' knowledge through disseminating information about nutrition recovery centers, conducting outreach regarding malnourished children, MP-ASI, Nutrition Aware Families and providing motivation to increase mothers' knowledge and awareness of the nutritional status of toddlers.